A Qur'an-Based Islamic Education Learning Management Model for Developing the Noble Character of High School Students - Fatma Sari; Hamdi Abdul Karim; Muhammad Afif Al-Faruq (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2024)
ENGLISH: A Qur'an-Based Islamic Education Learning Management Model for Developing the Noble Character of High School StudentsObjective: This study aims to determine the management model of Qur'an-based Islamic education learning at SMAN 5 Payakumbuh in fostering student character. Methods: A descriptive qualitative approach was employed. Data were collected through observation, in-depth interviews, and document analysis Source triangulation techniques were used for data validation. Results: The Qur'an-based Islamic education learning management model at SMAN 5 Payakumbuh effectively develop students’ character by emphasizing values such as honesty, discipline, responsibility, and cooperation. Conclusion: The integration of Qur'anic values into the management of Islamic education learning has led to positive transformations in students’ behaviors, both academically and socially. Contribution: This study provides valuable insight into the management of Islamic education grounded in Qur'anic values and offers a novel approach that can be adopted in both formal and non-formal educational settings to enhance character development.INDONESIAN: Model Manajemen Pembelajaran Pendidikan Islam Berbasis Al-Qur’an dalam Membangun Karakter Siswa SMATujuan: Penelitian ini bertujuan untuk mengetahui model manajemen pembelajaran pendidikan islam berbasis Al-Qur'an yang diagunkan di SMAN 5 Payakumbuh dalam membangun karakter siswa. Metode: Desain penelitian menggunakan metode kualitatif deskriptif. Metode observasi, wawancara mendalam, dan dokumentasi digunakan sebagai instrumen penelitian. Analisis data menggunakan teknik triangulasi sumber. Hasil: Model manajemen pembelajaran pendidikan islam berbasis Al-Qur'an di SMAN 5 Payakumbuh efektif dalam membentuk karakter siswa dengan menekankan nilai-nilai seperti kejujuran, kedisiplinan, tanggung jawab, dan kerja sama. Kesimpulan: Model manajemen pembelajaran pendidikan islam mengintegrasikan nilai-nilai Al-Qur'an berhasil menciptakan perubahan positif dalam sikap dan perilaku siswa, baik dalam konteks akademik maupun sosial. Kontribusi: Penelitian berkontribusi sebagai wawasan dan sumber ilmu pengetahuan tentang manajemen pembelajaran pendidikan islam berdasarkan nilai-nilai Al-Qur'an, serta memberikan pendekatan baru yang dapat diterapkan dalam berbagai konteks pendidikan, baik formal maupun nonformal, untuk memperkuat pembangunan karakter siswa.